LEARNING EXPERIENCES USING BLENDED LEARNING ON EFL LEARNERS AT SULAWESI BARAT UNIVERSITY - Putu Wahyu Sudewi (BASIS (Bahasa dan Sastra Inggris), 2020)
Blended learning is a mixed learning model between conventional learning or commonly called face-to-face and e-learning. This learning model utilizes an internet connection to do one of its components, namely online learning that utilizes certain applications. Based on that, the problems examined in this study are: (1) How did students feel about their blended learning experience, (2) What difficulties/challenges did students experience during their blended learning experience? This study aims to determine learning experiences and difficulties/challenges using blended learning models in EFL learners at the University of Sulawesi Barat and the type of ethnographic research that focuses on case studies. This study focuses on case studies in order to investigate deep phenomena regarding a case. Data are described descriptively. The subjects in this study are students or learners of English as a foreign language (EFL) at the University of Sulawesi Barat. Data collection methods are observation, interviews, and questionnaires addressed to EFL students. The validity of the data technique is the technique of triangulation. The result of this study represents 5 learning experiences that faced by all subjects. There were blended learning method made them more excited because can done everywhere, less embarrassing felt, flexible, motivate to active in learning, simplify and speed up the process of nonstop communication. Furthermore, difficulties/challenges faced by all subjects using the method was network connection an Four varying categories emerged and these included: managing time, technical issues, novelty of the learning experience, and learning style.